Kurangnya Minat Pembelajaran Sastra di Sekolah Menengah Atas Negeri 1 Panti Pasaman dan Peran Guru dalam Mengatasinya - Gustiana, Gustiana; Nurmaini, Nurmaini; Harlita, Harlita; Nova, Tetri Alia; Syofiani, Syofiani (Universitas Islam Sumatera Utara, 2025)
This study aims to analyze the lack of interest in literary learning, which significantly affects students’ writing skills. The research involved eleventh-grade students (Phase F) at Sekolah Menengah Atas Negeri 1 Panti Pasaman. Employing a qualitative descriptive method, the study presents data and findings in the form of narrative descriptions rather than numerical analysis. Literature reviews were conducted through relevant scholarly journals, proceedings, and reference books to establish a comprehensive foundation for the investigation. The research question focuses on identifying the underlying causes of low interest in literary learning and examining how teachers play a role in addressing these issues. The findings reveal that internal factors, such as intelligence, interest, talent, and personality, as well as external factors, including family, school, and community, contribute to students’ limited engagement with literary studies. Additionally, students with learning difficulties face further challenges that hinder their participation and performance. The study concludes that both internal and external dimensions must be addressed systematically, with teachers serving as key agents in fostering students’ interest and motivation in literary learning. These insights highlight the need for strategic pedagogical interventions to enhance the effectiveness of literature education and improve students’ writing competencies.